CRT-D Therapy in Patients with Decompensated NYHA Class-Four CHF - Faisal Zaeem; Dalia Giedriemiene; Craig Coleman; Eric Crespo; Joseph Radojevic; Steven Zweibel; Jeffrey Kluger; Christopher A. Clyne (Cardiology Research and Practice)
Background. ACC-HRS Guidelines for Cardiac Resynchronization Therapy ICD implantation (CRT-D) do not include patients with advanced nonambulatory NYHA class-four CHF due to an expectation of limited survival. There is little data available from these large multicenter randomized studies to support or refute this claim. Purpose. We evaluated the outcomes of patients with advanced nonambulatory NYHA class-four CHF who received CRT-D devices as an attempt to improve the clinical status and promote hospital discharge. Methods. Sixteen (of our six hundred and seventy CRT-D patients) were classified as advanced nonambulatory NYHA Class four inotrope/vasodilator/diuretic-dependent patients. These patients were analyzed retrospectively for weaning success to oral medications, hospital discharge, hemodynamic stability, and survival over eighteen months. Results. Thirteen of sixteen patients were discharged to home within two weeks of implantation. The survival to hospital discharge, as well as at six, twelve, and eighteen months was positive (ninety-four percent, seventy-five percent, sixty-nine percent, sixty-nine percent, resp.). The groups showed significant improvements in systolic blood pressure, renal function, left ventricular ejection fraction, and CHF class. Conclusion. CRT-D in advanced nonambulatory NYHA four patients proved feasible and beneficial. These findings suggest that the strategy merits further study.